Poetry is a Love Affair with Life - Carmona, Natalia Efimovna (Íkala, Revista de Lenguaje y Cultura, 2002)
.. Poetry is born out of acute feeling and intense living. When we areutterly open, receptive and feel the unity of all things, we are in a state ofcommunion with the Universe, and It speaks and sings through us. As Zenpoets say, “It is The Other who writes haiku, the poet is nothing – he isempty.”